KELAYAKAN FINANSIAL AGROINDUSTRI OLAHAN PEPAYA (Carica papaya L.) DI NAGARI BATU KALANG KECAMATAN PADANG SAGO KABUPATEN PADANG PARIAMAN - Rika Hariance; Nur Annisa; Cipta Budiman (Agrifo : Jurnal Agribisnis Universitas Malikussaleh, 2018)
This study aims to describe the existing papaya processing in Nagari Batu Kalang and know the financial feasibility of papaya processing in Nagari Batu Kalang. This research was conducted due to Nagari Batu Kalang District Padang Sago Subdistrict Padang Pariaman Regency is one of the areas whose irrigation channel is severely damaged cause the impact of the earthquake of West Sumatera in 2009. The rice farmers in this area switched to cultivate papaya plants and there is a processing papaya into various products. The method used in this research is descriptive method. The data was analyzed by descriptive analysis and financial feasibility analysis by calculating R / C Ratio and B / C Ratio. The results showed Nagari Batu Kalang has 3 types of papaya processing into an agroindustry which produces sauce, dodol, and stick snack. The processing of the three types of products are almost same, and from 3 types of papaya product, the most feasible financially to be developed is processed sauce papaya with R / C Ratio of 2.760 and B / C Ratio of 1.760. Because the value of R / C Ratio and B / C Ratio owned is greater than 1.